2021
DOI: 10.1186/s12877-021-02101-4
|View full text |Cite
|
Sign up to set email alerts
|

Frailty status as a potential factor in increased postoperative opioid use in older adults

Abstract: Background Prescription opioids are commonly used for postoperative pain relief in older adults, but have the potential for misuse. Both opioid side effects and uncontrolled pain have detrimental impacts. Frailty syndrome (reduced reserve in response to stressors), pain, and chronic opioid consumption are all complex phenomena that impair function, nutrition, psychologic well-being, and increase mortality, but links among these conditions in the acute postoperative setting have not been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…On the one hand, frailty has been associated with behaviors which may increase ocular disease risk, such as low physical activity [ 16 ]. On the other hand, older adults with frailty usually take opioids to relieve disease-related pain symptom, which may cause damage to vision [ 17 ]. Therefore, vision impairment and frailty may be linked in a two-way fashion, which may produce a downward spiral, where each in turn triggers the other.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, frailty has been associated with behaviors which may increase ocular disease risk, such as low physical activity [ 16 ]. On the other hand, older adults with frailty usually take opioids to relieve disease-related pain symptom, which may cause damage to vision [ 17 ]. Therefore, vision impairment and frailty may be linked in a two-way fashion, which may produce a downward spiral, where each in turn triggers the other.…”
Section: Introductionmentioning
confidence: 99%
“… 28 Furthermore, in the population above 65 years, high frailty rather than younger age is the primary predictor for increased postoperative opioid consumption. 29 Patients randomized to the SAPB group in our study appeared to be more frail as indicated by their lower SF-36 physical component summary scores. 30 However, they consumed significantly less opioids in the postoperative phase.…”
Section: Discussionmentioning
confidence: 58%
“…Frailty prior to surgery has been associated with postoperative acute pain and CPSP at 3 months after surgery; however, these mechanisms are poorly documented (Alvarez‐Nebreda et al, 2018; Auckley et al, 2021). Although few reports have investigated the relationship between functional disability measured using the WHODAS 2.0 and frailty instruments, 12‐item WHODAS 2.0 scores moderately correlated with activities of daily living in outpatients and surgical patients (Fujiwara et al, 2021; Ida et al, 2017).…”
Section: Discussionmentioning
confidence: 99%